(CF3CO)2O/CF3SO3H-mediated synthesis of 1,3-diketones from carboxylic acids and aromatic ketones - Kim, JungKeun; Shokova, Elvira; Tafeenko, Victor; Kovalev, Vladimir (Beilstein Journal of Organic Chemistry, 2014)
A very simple and convenient reaction for 1,3-diketone preparation from carboxylic acids and aromatic ketones in TFAA/TfOH system is described. When the β-phenylpropionic acids were used as starting materials, they initially gave 1-indanones and then underwent further acylation with the formation of 2-(β-phenylpropionyl)-1-indanones as the main reaction products. In addition, the application of the proposed protocol allowed for the synthesis of selected polysubstituted pyrazoles in a one-pot procedure directly from acids and ketones.
Keywords: Claisen condensation; 1,3-diketones; heterocycles; triflic acid; trifluoroacetic acid anhydride

(untitled) - Kel’in, A. V. (Curr. Org. Chem., 2003)

(untitled) - Kel’in, A. V.; Maioli, A. (Curr. Org. Chem., 2003)

(untitled) - Vigato, P. A.; Peruzzo, V.; Tamburini, S. (Coord. Chem. Rev., 2009)

(untitled) - Katritzky, A. R.; Pastor, A. (J. Org. Chem., 2000)

(untitled) - Katritzky, A. R.; Wang, Z.; Wang, M.; Wilkerson, C. R.; Hall, C. D.; Akhmedov, N. G. (J. Org. Chem., 2004)

(untitled) - Shen, Z.; Li, B.; Wang, L.; Zhang, Y. (Tetrahedron Lett., 2005)

(untitled) - Katritzky, A. R.; Meher, N. K.; Singh, S. K. (J. Org. Chem., 2005)

(untitled) - Heler, S. T.; Natarajan, S. R. (Org. Lett., 2006)

(untitled) - Iida, A.; Osada, J.; Nagase, R.; Misaki, T.; Tanabe, Y. (Org. Lett., 2007)

(untitled) - Lim, D.; Fang, F.; Zhou, G.; Coltart, D. M. (Org. Lett., 2007)

(untitled) - Zhou, G.; Lim, D.; Coltart, D. M. (Org. Lett., 2008)

(untitled) - Sharma, A. K.; Subramani, A. V.; Gorman, C. B. (Tetrahedron, 2007)

(untitled) - Rendy, R.; Zhang, Y.; McElrea, A.; Gomez, A.; Klumpp, D. A. (J. Org. Chem., 2004)

(untitled) - Prakash, G. K. S.; Yan, P.; Török, B.; Olah, G. A. (Catal. Lett., 2003)

(untitled) - Yamato, T.; Hideshima, C.; Prakash, G. K. S.; Olah, G. A. (J. Org. Chem., 1991)

(untitled) - Dallemagne, P.; Rault, S.; Pilo, J. C.; Foloppe, M. P.; Robba, M. (Tetrahedron Lett., 1991)

(untitled) - Hulin, B.; Koreeda, M. (J. Org. Chem., 1984)

(untitled) - Premasagar, V.; Palaniswamy, V. A.; Eisenbraun, E. J. (J. Org. Chem., 1981)

(untitled) - Luke, G. P.; Seekamp, C. K.; Wang, Z.-Q.; Chenard, B. L. (J. Org. Chem., 2008)

(untitled) - Pal, S.; Khan, M. A.; Bindu, P.; Dubey, P. K. (Beilstein J. Org. Chem., 2007)

(untitled) - Gray, A. D.; Smyth, T. P. (J. Org. Chem., 2001)

(untitled) - Galli, C. (Synthesis, 1979)

(untitled) - Plażuk, D.; Zakrzewski, J.; Salmain, M. (Org. Biomol. Chem., 2011)

(untitled) - Plażuk, D.; Zakrzewski, J. (J. Organomet. Chem., 2009)

(untitled) - Plażuk, D.; Zakrzewski, J. (Synth. Commun., 2004)

(untitled) - Kovalev, V.; Shokova, E.; Shmailov, A.; Vatsouro, I.; Tafeenko, V. (Eur. J. Org. Chem., 2010)

(untitled) - Kost, A. N.; Grandberg, I. I. (Adv. Heterocycl. Chem., 1966)

(untitled) - Burton, H.; Munday, D. A. (J. Chem. Soc., 1957)

(untitled) - Fattakhov, S. A.; Tarasova, R. I.; Voskresenskaya, O. V.; Gazizov, M. B. (Russ. J. Gen. Chem., 2010)